(883) Priorities in health planning: A general framework أولويات التخطيط الصحي- إطار عام - Hassouna, W. A. (The Institute of National Planning, 2025)
optimize a specific preference function, which reflects the desires of political authority—whether a dictator, influential group, or parliament. This preference function is a complex of various priorities that indicate the importance attached to each desire. The arrangement of these priorities significantly influences the solutions developed; any change in this arrangement will lead to different outcomes. When a suitable solution is adopted, the preliminary priorities become definitive, and this solution is termed "The Plan." If the solution is rejected, the priorities must be rearranged to find a new solution. The differences between solutions highlight variations in preference functions and can be quantified as the costs associated with changing priorities. Hence, determining priorities is crucial in the planning process.